Obesity, Fatty Liver and Liver Cancer (Advances in Experimental Medicine and Biology,, 2018)
This volume covers a state-of-the-art illustration of recent discoveries concerning obesity-related fatty liver diseases and liver cancer. The contents are extensive and comprehensive. It brings important topics in the field all together under one umbrella, from epidemiology and etiology, molecular pathogenesis, cellular biology, epigenetics, immunology, microbiology, animal models to therapeutic approaches and treatments. All the book contributors are leading experts in the field. It will appeal to researchers, clinicians and graduate students in obesity, fatty liver diseases, GI/Liver cancer field. It may also yield benefits for pharmaceutical companies with regard to drug discovery.